Kepemimpinan sekolah berbasis pendidikan multikultural - Miftahus Sa'adah (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2018)
Pendidikan multikultural yang diintegrasikan dalam pendidikan formal di sekolah urgen diterapkan di Indonesia mengingat keragaman budaya yang dimilikinya. Sekolah hendaknya menjadi wadah yang efektif bagi penanaman sikap multikultural siswa sebagai generasi penerus bangsa. Akan tetapi dalam kenyataannya, sekolah masih belum mampu secara efektif menumbuhkan jiwa multikultural siswa terbukti dengan maraknya fenomena perkelahian antar pelajar. Disisi lain, kepala sekolah merupakan ujung tombak dan pelopor bagi penciptaaan lingkungan dan budaya multikultural dalam sekolah. Artikel ini membahas tentang model kepemimpinan sekolah yang diharapkan dapat merancang, menumbuhkan, mengimplementasikan dan memelihara budaya multikultural di sekolah yang pada gilirannya dapat membentuk pribadi-pribadi siswa yang ramah dan menghargai perbedaan dan keragaman. Kesimpulan dalam artikel ini menyatakan bahwa model kepemimpinan transformasional diharapkan dapat membawa perubahan, menginspirasi sekaligus menjadi role model bagi terciptanya budaya yang menjunjung tinggi nilai-nilai persatuan dalam keragaman yang sesuai dengan tujuan pendidikan multikultural di Indonesia.Kata kunci: kepemimpinan transformasional, kepala sekolah, pendidikan multikultural SCHOOL LEADERSHIP BASED ON MULTICULTURAL EDUCATIONAbstractConsidering the massive diversity of Indonesian cultures, multicultural education integrated within schools as the arrangement of formal education is urgently implemented. Preferably, schools should develop into an effective place for building students’ multicultural attitude. However, it is a contrasting fact that schools have not been able to effectively establish students’ awareness of multicultural reality. This is evidenced by the growing number of students’ brawls taking place throughout Indonesia. Nonetheless, school’ principal is expected to be the pioneer in creating values and practices of multiculturalism in school context.  This paper discusses the anticipated model of school leadership that likely to be able to design, build, implement, and foster multiculturalism in school which further develops into shaping students’ attitude demonstrating high respect toward pluralism and diversity. It is concluded that transformational leadership is expected to make changes, inspire as well as be the role model for the creation of multiculturalism appreciating the value of unity among diversity appropriate to the purpose of multicultural education in Indonesia.Keywords: transformational leadership, school principal, multicultural education